Symbols of the Animal Designs of Kurdistan Glim - Sara Sadeghi; Reza Rezalou; Farzad Feizi (پژوهشنامه ادبیات کردی, 2020)
Iran, with its many ethnicities, has a remarkable art in the context of glim. West of Iran, especially in Kurdistan province, this art is full of various manifestations of planning. In the province of Kurdistan, with the woven machinery and the widespread factory production, which often overshadows the handicrafts, it is still found in villages and among the glimbafi tribes, so Kurdish glimmers are no exception and the industry is slowly being forgotten. The importance of this art and the symbolic type of paintings woven into the text of the caricature calls for the necessity and importance of this research. The present article examines the animal motifs of Kurdish carpets and the symbols of animal carpets in the carpets of Kurdistan province. Hence (3 samples of cartridges) were purposively selected. This article is a descriptive-analytical one and the data collection from library sources and field sample identification is obtained. These symbols convey different meanings about Kurdish culture. The motifs include animal, geometric, tooling and plant motifs, which are discussed in this article. The woven roles in this art are based on the nature of his life and his modeling of beliefs and roots in the beliefs of the Kurdish people.